PEMAKAIAN VERBA BERMAKNA MEMOTONG DALAM BAHASA MELAYU MUSI OLEH PELADANG DI KABUPATEN BANYUASIN - naqeza, naqeza (Salingka, 2018)
The use of verbs meant cutting by peladang have been decreased as an impact of agriculture modernization system. This research aims at showing and conservate how the verbs meant cutting are used. The method used is decriptive qualitative with three strategic steps, those are data collecting, data analizing, and research result. The results show that the verbs meant cutting were found in term of cutting objek using tools, such menutoh, menetak, memancong, menjempong, mengerap, merandan, menyeset, menyiang, melelet, menyiser, menuntong, menumang, melayang, meruntoh, meriding, mengarit, menyesap, menunas, menyuguh, mengetam, mengocek, mengelanit, mengelayak, mencantiki, meruntun, memunggam, dan mengumbuti. Then, the verbs meant cutting are not using tool, such as mengenas, menyuer, merurut, menyentak, menyentut, menggetel, memuler, menggetas, memokel, and mengirek. Then, based on the object to be cut in the horizontal, verticle, and diagonal. In short, the verbs meant cutting can be used based on the position of the object and the tool used to cut.